Implementasi Blended Learning dalam Meningkatkan Kemandirian Belajar Siswa pada Mata Pelajaran PAI di SMA UII Banguntapan - Sagala, Hairun Hasanah; Muh Wasith Achadi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2022)
This study aims to determine the process of implementing blended learning in increasing student independence in PAI subjects at SMA UII Banguntapan. This type of research uses a mixed method using a sequential mixed methods strategy, especially an exploratory sequential strategy. The subjects in this study were class X students, totaling 98 students with the sampling technique using the case’s technique. While the instruments used are interviews, observations, documentation, and questionnaires. The results of the research found that the process of implementing blended learning at the UII Banguntapan High School had been running effectively and smoothly and the implications obtained during blended learning were that students had an attitude of independence, including an attitude of confidence, responsibility, free behavior, self-control, discipline, as well as creativity and initiative.